Differences in urinary incontinence symptoms and pelvic floor structure changes during pregnancy between nulliparous and multiparous women - Luo, Dan; Chen, Ling; Yu, Xiajuan; Ma, Li; Chen, Wan; Zhou, Ning; Cai, Wenzhi (PeerJ, 2017)
Background This study was performed to compare changes in urinary incontinence (UI) symptoms and pelvic floor structure during pregnancy between nulliparous and multiparous women. Methods A cross-sectional survey was performed among pregnant women from July 2016 to January 2017. In total, 358 pregnant women from two hospitals underwent an interview and pelvic floor transperineal ultrasound assessment. A questionnaire regarding sociodemographic, gynecological, obstetric features and the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) were used for the interview. Imaging data sets were analyzed offline to assess the bladder neck vertical position (BNVP), urethral angles (α, β, and γ angles), and hiatal area (HA) at rest and at maximal Valsalva maneuver (VM). Results After excluding 16 women with invalid data, 342 women were included. The prevalence (χ2 = 9.15, P = 0.002), frequency (t = 2.52, P = 0.014), usual amount of UI (t = 2.23, P = 0.029) and scores of interference with daily life (t = 2.03, P = 0.045) during pregnancy were higher in multiparous than nulliparous women. A larger bladder neck descent (BND) (F = 4.398, P < 0.001), HA (F = 6.977, P < 0.001), α angle (F = 2.178, P = 0.030), β angle (F = 4.404, P < 0.001), and γ angle (F = 2.54, P = 0.011) at VM were discovered in pregnant women with UI than without UI. Multiparous women had a significantly higher BND (t = 2.269, P = 0.024) and a larger α angle (F = 2.894, P = 0.004), β angle (F = 2.473, P = 0.014), and γ angle (F = 3.255, P = 0.001) at VM than did nulliparous women. Conclusion Multiparous women experienced more obvious UI symptoms and pelvic floor structure changes during pregnancy than did nulliparous women.
Keywords: Urinary incontinence; Nulliparous; Multiparous; Transperineal ultrasound